The Effect of Pop-up Dictionary Tools for Vocabulary Learning Aid on the "Language Reactor" Chrome Web Extension - Lifa Nur Cahyani; Mutiara Bilqis; Areta Puspa (Indonesia Technology-Enhanced Language Learning (iTELL) Journal, 2024)
Language application to learn vocabulary has gained a lot interest in the past years including “Language Reactor”, a Chrome web extension based application. This extension offering learning language through movies or videos using dual subtitles and pop-up dictionary. Previous studies focuses on the Pop-up dictionary tools showed benefit for vocabulary learning aids integrated with reading skills, while the research about the benefit of Pop-up dictionary for vocabulary learning aids integrated with listening skills is limited. This research aimed to know the effect of Pop-up dictionary tools in “Language Reactor” for vocabulary learning aid that integrated with listening skills. Using quasi-experimental research design, the population were divided into two groups with the experimental group using “Language Reactor” and the control group using “GOM Player”to viewing the video materials. Pretests in the form of vocabulary tests were administered before the four-meeting experiment in a public senior high school in Indonesia, followed by posttest for both group. Because the data obtained show unpaired sample size, the Independent Samples T-test was used to analyze the data. The result revealed that the significant value (2-tailed) was 0.522, indicating that there was no positive effect on the use of Pop-up dictionary in the “Language Reactor” Chrome extension as vocabulary learning aid. This demonstrates that using technology in the classroom do not always enhanced learning. Therefore, carefully choosing the technology to use for learning vocabulary in the classroom is suggested, particularly when integrated with different language skills.